2012
DOI: 10.1073/pnas.1207605109
|View full text |Cite
|
Sign up to set email alerts
|

Control of mitochondrial metabolism and systemic energy homeostasis by microRNAs 378 and 378*

Abstract: Obesity and metabolic syndrome are associated with mitochondrial dysfunction and deranged regulation of metabolic genes. Peroxisome proliferator-activated receptor γ coactivator 1β (PGC-1β) is a transcriptional coactivator that regulates metabolism and mitochondrial biogenesis through stimulation of nuclear hormone receptors and other transcription factors. We report that the PGC-1β gene encodes two microRNAs (miRNAs), miR-378 and miR-378*, which counterbalance the metabolic actions of PGC-1β. Mice genetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
271
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(290 citation statements)
references
References 51 publications
18
271
1
Order By: Relevance
“…In addition, we also checked the expression of two known miR-378/378* targets, carnitine O-acetyltransferase (Crat) and mediator complex subunit 13 (Med13). Consistent with the previously reported result 21 , the expression levels of both Crat and Med13 in the liver of 378KO mice on normal chow were not altered ( Supplementary Fig. 6j).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, we also checked the expression of two known miR-378/378* targets, carnitine O-acetyltransferase (Crat) and mediator complex subunit 13 (Med13). Consistent with the previously reported result 21 , the expression levels of both Crat and Med13 in the liver of 378KO mice on normal chow were not altered ( Supplementary Fig. 6j).…”
Section: Resultssupporting
confidence: 92%
“…In breast cancer, miR-378* upregulation results in an increase in cell proliferation and lactate production, and a repression of tricarboxylic acid cycle and oxygen consumption, indicating that miR-378* is able to mediate metabolic shift in cancer cells 20 . It has also been reported that hepatic miR-378/378* expression is dysregulated in a rat model of type 2 diabetes and obese mouse models, including genetic ob/ob mice and mice fed a high-fat diet 15,21,22 . However, whether and how miR-378 or miR-378* plays a regulatory role in hepatic glucose and lipid metabolism remains unclear.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Among these varied biological responses, a common mechanism of action appears to be the promotion of oxidative metabolism accompanying the stimulation of mitochondria biogenesis. The promotion of fatty acid oxidative metabolism leads to a reduction of fat accumulation in muscle, which, in turn, increases insulin sensitivity and the glucose uptake by insulin-sensitive tissues [64].PGC1-β is encoded by the Ppargc1b gene and is preferentially expressed in tissues with relatively high mitochondrial content, including heart, slow skeletal muscle and BAT [3]. PGC1-β knockout mice display an altered expression in a large number of nuclear-encoded genes that regulate mitochondria energy metabolism in multiple tissues and these mice are extremely sensitive to cold exposure and develop hepatic steatosis upon feeding with high fat diet [69,73].…”
mentioning
confidence: 99%
“…In fact, the number of overweight and obese people rose from 857 million in 1980 to 2.1 billion in 2013 [2]. Recently, obesity and metabolic syndrome were associated with mitochondrial dysfunction and deranged regulation of metabolic genes [3]. Interestingly, mitochondria of obese individuals seem to be different from those of lean individuals.…”
mentioning
confidence: 99%